2006
DOI: 10.1021/cm061580n
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of Ce3+ and Oxygen Vacancies in Cerium Oxide Nanoparticles

Abstract: Temperature variations of the electron magnetic resonance (EMR) spectra and magnetization measurements are used to show that Ce3+ ions in concentration ≃18% are present in 3 nm CeO2 nanoparticles supported on silica aerogel. It is argued that the presence of Ce3+ implies the defect structure CeO2- x for ceria nanoparticles due to oxygen vacancies. This transformation of Ce4+ to Ce3+ driven by oxygen vacancies may be the key to understanding the catalytic properties of ceria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
225
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 367 publications
(240 citation statements)
references
References 18 publications
14
225
0
1
Order By: Relevance
“…However, its structural properties allow CeONP to be restored to its initial state. 32 The kinetics measured by Seal et al 43 showed excellent activity for CeONP (3-5 nm), with a constant catalytic rate that exceeded the one determined for the enzyme SOD.…”
Section: The Multi-enzyme Mimetic Activities Of Ceonpmentioning
confidence: 90%
See 2 more Smart Citations
“…However, its structural properties allow CeONP to be restored to its initial state. 32 The kinetics measured by Seal et al 43 showed excellent activity for CeONP (3-5 nm), with a constant catalytic rate that exceeded the one determined for the enzyme SOD.…”
Section: The Multi-enzyme Mimetic Activities Of Ceonpmentioning
confidence: 90%
“…31 In general, the fraction of Ce 3 þ ions in the particles increases with decreasing particle size. The techniques used to determine the Ce 3 þ /Ce 4 þ ratios include X-ray photoelectron spectroscopy, 31 X-ray absorption nearedge spectroscopy, 32 electron magnetic resonance spectroscopy 33 and UV-visible absorption spectroscopy. 34 It is remarkable and interesting that CeONP could have a dual role as an oxidation catalyst and reduction catalyst, depending on the reaction conditions.…”
Section: The Multi-enzyme Mimetic Activities Of Ceonpmentioning
confidence: 99%
See 1 more Smart Citation
“…Starting chemicals used for the synthesis of powders were strontium nitrate Sr(NO 3 ) 3 , cerium nitrate hexahydrate [Ce(NO 3 ) 3 ·6H 2 O] and glycine (NH 2 CH 2 COOH) from Wako Chemical Industries, Ltd., Japan. The compositions of the starting reacting mixtures were calculated according to the nominal composition of the final reaction product.…”
Section: Methodsmentioning
confidence: 99%
“…1͑a͔͒ of the CeO 2 , synthesized using coprecipitation method exhibits characteristic diffraction planes corresponding to CeO 2 fluorite structure. 2,15 However, the observed reflection planes are broad due to small particle size ͑ϳ10 nm͒ estimated using Scherrer's formula. The incorporation of NanoCeO 2 in CH matrix has been confirmed using SEM wherein, regular planner morphology of CH ͑Ref.…”
mentioning
confidence: 99%